UTILIZATION OF SOCIAL MEDIA AS A HOTEL MARKETING TOOL IN BANDUNG CITY - Dewi Indriani Jusuf (Jurnal Multidisiplin Sahombu, 2023)
The city of Bandung is known as one of the popular tourist destinations in Indonesia, with a number of varied hotels competing in the hospitality industry. Social media has become an important platform in marketing strategies in various sectors, including the hospitality industry. This research aims to explore and analyze the use of social media as an effective marketing tool for hotels located in the city of Bandung. This research uses a qualitative approach with descriptive methods. The research results show that the use of social media as an effective marketing strategy has become an important key for the hotel industry in developing and maintaining their brand presence amidst increasingly fierce competition. By leveraging social media, hospitality brands can leverage a variety of tools, including targeted advertising, reputation management, and high-quality content, to capture customer attention, increase engagement, and drive increased bookings and sales. In optimizing the use of social media, it is important for hospitality brands to ensure that interactions with customers remain responsive, positive and informative, as well as ensure that the user journey from social media to the booking platform runs smoothly. Thus, social media is not only a powerful marketing tool, but also an important tool in building strong relationships between hospitality brands and their customers, generating extraordinary experiences and creating unforgettable impressions for users.